The Importance and Control of Low-Grade Inflammation Due to Damage of Cellular Barrier Systems That May Lead to Systemic Inflammation - Rönnbäck, Cecilia; Hansson, Elisabeth (Frontiers in Neurology, 2019)
Systemic low-grade inflammation can be initiated in vivo after traumatic injury or in chronic diseases such as neurodegenerative, metabolic and autoimmune diseases. Inducers of inflammation trigger production of inflammatory mediators, which alter the functionality of tissues and organs and leads to harmful induction of different barrier systems in the body, where the blood-brain barrier, the blood-retinal barrier, blood-nerve barrier, blood-lymph barrier and the blood-cerebrospinal fluid barrier play major roles. The different barriers are unique but structured in a similar way. They are equipped with sophisticated junctional complexes where different connexins, protein subunits of gap junction channels and hemichannels, constitute important partners. The cells involved in the various barriers are coupled in networks, are excitable but do not express action potentials and may be targets for inflammation leading to changes in several biochemical cellular parameters. During any type of inflammation barrier break-down is observed. In the present review we want to highlight the importance and control of different barriers where any form of injury may lead to systemic inflammation.